Virtual Reality in Education: Immersive Learning for Deeper Understanding - Khurshed Iqbal; Oratilwe Penwell Mokoena; Ayenew Kassie Tesema; Jihad Jaafar Waham (EDUJAVARE: International Journal of Educational Research, 2025)
Integrating Virtual Reality (VR) in education presents a promising opportunity to enhance immersive learning and deepen student understanding of complex subjects. Despite its potential, the widespread adoption of VR in classrooms remains limited due to challenges such as high costs, inadequate teacher training, and the difficulty in aligning VR with existing curricula. This study aims to explore the impact of VR on student engagement, conceptual understanding, and learning outcomes across diverse educational settings. A qualitative approach was employed, involving semi-structured interviews, participant observations, and document analysis with students, teachers, and curriculum developers at two secondary schools and one university in Jakarta, Indonesia. The findings reveal that VR significantly enhances student engagement, promotes deeper conceptual understanding, and fosters emotional connections to learning materials. However, challenges related to technological infrastructure, teacher readiness, and curriculum integration were also identified. The study concludes that while VR has substantial educational benefits, its successful implementation requires overcoming these barriers through targeted training, improved content design, and a more systematic approach to curriculum integration. This research contributes to the growing knowledge of educational technologies, offering practical insights into how VR can effectively transform teaching and learning practices.